Plant Extracts in Development of Medicinal Products of Various Therapeutic Value - I. P. Smirnova; O. A. Semkina; O. V. Bondarenko (Антибиотики и Химиотерапия, 2020)
Development, standardization and use of medicinal products of plant origin and various therapeutic value are described in the review. The literature data refer to the studies of some leading institutions of the Russian Federation and in particular to the Medical Institute of the Russian University of Peoples' Friendship, All-Russian Research Institute of Medicinal and Aromatic Plants, Pyatigorsk State Pharmaceutical Academy and some foreign laboratories. Possible use of the trichoderma extract and its prospects are shown.